Seeing through the skin: dermal light sensitivity provides cryptism in moorish gecko. (1st July 2014) - Fulgione, D.; Trapanese, M.; Maselli, V.; Rippa, D.; Itri, F.; Avallone, B.; Van Damme, R.; Monti, D. M.; Raia, P.
Abstract Concealment by means of colour change is a pre‐eminent deceptive mechanism used by both predators and prey. The moorish gecko Tarentola mauritanica is able to blend into the background by either darkening or paling according to the substrate darkness. Here we examined the functioning of background perception in moorish gecko. We experimentally excluded the involvement of melanophore‐stimulating hormone in camouflage. Blindfolded individuals change their colour consistently with the background. Surprisingly, individuals with covered flanks were not able to change colour, no matter whether they were allowed to see the substrate or not. Accordingly, we found high levels of opsin transcript and protein in the flank region of the gecko. These observations suggest that T. mauritanica skin melanophores are able to activate a process of colour change autonomously. This study yields the first evidence of crypsis mediated by dermal light sensitivity in amniotes.